Current trends in tonsillitis and tonsillectomy - Millington, AJ (Ann R Coll Surg Engl, 2014)
INTRODUCTION: The aim of this study was to assess tonsillitis and tonsillectomy trends, both from a local and national perspective. METHODS: Retrospective analysis was carried out of tonsillitis admissions and tonsillectomy rates over a ten-year period in a university teaching hospital from 2003 to 2012. RESULTS: Since 2003 tonsillitis admissions have increased locally by 118% in adults and 179% in children despite negligible changes in tonsillectomy rates. Similar trends have been observed nationally. CONCLUSIONS: The findings of this study may be considered to be the result of current National Health Service policy. A reconsideration of agreed indications for tonsillectomy could potentially reduce hospital admissions of patients with tonsillitis in the long term.